2012
DOI: 10.1519/jsc.0b013e31822dd3ac
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Body Mass Index and Fitness Levels Among Schoolchildren

Abstract: Childhood obesity is an epidemic in the U.S.A., and understanding aspects of fitness is critical in implementing effective interventions. The purpose of this study was to analyze the relationship of obesity levels with the fitness levels of public school children in Louisiana. Over 7,000 school children participated in body mass index (BMI) and Fitnessgram® subtests including the Progressive Aerobic Cardiovascular Endurance Run (aerobic capacity), curl-ups, trunk lifts, push-ups (strength and endurance), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 24 publications
3
22
2
6
Order By: Relevance
“…Previous studies report lower physical fitness levels, using the PACER, in obese children compared with nonobese peers; however, mean data were not reported [20]. In our overall sample, the mean PACER score was 13.4 laps, which is lower than the mean fitness level of 29.7 laps from a large school-based population [6].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Previous studies report lower physical fitness levels, using the PACER, in obese children compared with nonobese peers; however, mean data were not reported [20]. In our overall sample, the mean PACER score was 13.4 laps, which is lower than the mean fitness level of 29.7 laps from a large school-based population [6].…”
Section: Discussioncontrasting
confidence: 85%
“…Despite these recommendations, the time spent in physical activity and participating in sports is low in obese and overweight children when compared with healthy-weight children [21,49]. In a recent cohort study of over 7000 5 to 17 year olds, of whom 40% were classified as overweight (18%) or obese (22%) by BMI, obese children demonstrated lower physical fitness levels (measured by the Progressive Aerobic Cardiovascular Endurance Run [PACER]) compared with healthyweight children [20]. The relationships of factors such as musculoskeletal pain that may interfere with physical fitness or physical activity levels are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The review highlighted the sit and reach test with a number of 14 records found [63,118,128,139,[179][180][181][182][183][184][185][186] -the lowest point reached by the fingertips while standing on a box with legs extended with 1 record found [149], the V-sit and reach with 1 record found [187] and the shoulder stretches with 2 records found [117,188] (Table 6). …”
Section: Muscular Endurancementioning
confidence: 99%
“…Estudios realizados en Chile han demostrado que los escolares obesos presentan un perímetro de cintura más elevado, necesitan mayor tiempo para recorrer 400 metros y poseen niveles aumentados de glucosa basal (30), se ha descrito en escolares americanos, que un IMC saludable se asocia a mejores niveles de condición física (31).…”
Section: Discussionunclassified